Kebijakan Perlindungan Dan Pengelolaan Lingkungan Hidup - Adolf Liku, Adolf Liku; Saputera, Dharma; Mulya, Widya (EUNOIA, 2022)
Humans and natural resources cannot be separated because they are one unit. In Article 1 point 9 of Law Number 32 of 2009 concerning Environmental Protection and Management, hereinafter referred to as UUPPLH explains that natural resources are elements of the environment consisting of biological and non-biological resources which as a whole form a unified ecosystem. The method used in the delivery of service material is a workshop (question and answer) delivery of material from tutors using a zoom meeting. The target that we will achieve related to the implementation of this community service is to increase public knowledge about environmental protection and management, so that people know and are able to actually apply environmental conservation actions in their daily lives. In addition, the output of the results of this service will be made into articles to be published in community service journals.